Misfolded α-synuclein causes hyperactive respiration without functional deficit in live neuroblastoma cells - Cathryn L. Ugalde; Sarah J. Annesley; Shane E. Gordon; Katelyn Mroczek; Matthew A. Perugini; Victoria A. Lawson; Paul R. Fisher; David I. Finkelstein; Andrew F. Hill (The Company of Biologists, 2020)
The misfolding and aggregation of the largely disordered protein, α-synuclein, is a central pathogenic event that occurs in the synucleinopathies, a group of neurodegenerative disorders that includes Parkinson's disease. While there is a clear link between protein misfolding and neuronal vulnerability, the precise pathogenic mechanisms employed by disease-associated α-synuclein are unresolved. Here, we studied the pathogenicity of misfolded α-synuclein produced using the protein misfolding cyclic amplification (PMCA) assay. To do this, previous published methods were adapted to allow PMCA-induced protein fibrillization to occur under non-toxic conditions. Insight into potential intracellular targets of misfolded α-synuclein was obtained using an unbiased lipid screen of 15 biologically relevant lipids that identified cardiolipin (CA) as a potential binding partner for PMCA-generated misfolded α-synuclein. To investigate whether such an interaction can impact the properties of α-synuclein misfolding, protein fibrillization was carried out in the presence of the lipid. We show that CA both accelerates the rate of α-synuclein fibrillization and produces species that harbour enhanced resistance to proteolysis. Because CA is virtually exclusively expressed in the inner mitochondrial membrane, we then assessed the ability of these misfolded species to alter mitochondrial respiration in live non-transgenic SH-SY5Y neuroblastoma cells. Extensive analysis revealed that misfolded α-synuclein causes hyperactive mitochondrial respiration without causing any functional deficit. These data give strong support for the mitochondrion as a target for misfolded α-synuclein and reveal persistent, hyperactive respiration as a potential upstream pathogenic event associated with the synucleinopathies. This article has an associated First Person interview with the first author of the paper.